1982
DOI: 10.1007/bf00543961
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-containing innervation of the human intestinal mucosa

Abstract: The three-dimensional distribution of the peptide-containing innervation in the human intestinal mucosa was studied by fluorescence immunohistochemistry on whole-mount mucosal preparations. An extensive VIP-immunoreactive nerve supply was demonstrated at all levels, but was markedly increased in density in the distal intestine, where it formed a particularly rich network in close contact with the luminal epithelium. In contrast, substance P-containing nerve fibres formed a looser and evenly distributed innerva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…In the human jejunum and ileum, VIP‐containing neurones extend into the mucosa where they form a dense network in contact with the luminal epithelium (Ferri et al ., 1982). Although the secretory action of VIP is well characterized the VIP‐containing nerves are more abundant in the villus (an area where absorption is more pronounced) than crypt region (Ferri et al ., 1982). Consistent with the distribution of VIP‐containing nerves, the VIP receptor on the intestinal enterocyte is found solely on the basolateral membrane (Dharmsathaphorn et al ., 1983) and in human jejunal membranes is more abundant (7–8×) in villus than crypt cells (Salomon et al ., 1993).…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…In the human jejunum and ileum, VIP‐containing neurones extend into the mucosa where they form a dense network in contact with the luminal epithelium (Ferri et al ., 1982). Although the secretory action of VIP is well characterized the VIP‐containing nerves are more abundant in the villus (an area where absorption is more pronounced) than crypt region (Ferri et al ., 1982). Consistent with the distribution of VIP‐containing nerves, the VIP receptor on the intestinal enterocyte is found solely on the basolateral membrane (Dharmsathaphorn et al ., 1983) and in human jejunal membranes is more abundant (7–8×) in villus than crypt cells (Salomon et al ., 1993).…”
Section: Introductionsupporting
confidence: 54%
“…Although intestinal function is highly regulated by a variety of neuroendocrine factors, relatively little is known about control of endogenous nutrient transporters. VIP is expressed abundantly throughout the submucosal plexus and in neurones which extend towards the intestinal epithelium and in particular the villus cells (Ferri et al ., 1982). Although VIP is a potent activator of Cl − and fluid secretion in intestinal epithelial cells it also reduces Na + absorption (Schwartz et al ., 1974; Krejs et al ., 1980).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies showed scattered ENK-immunoreactive nerve fibres in the mucosa (Ferri et al 1982(Ferri et al , 1984Keast et al 1985) but a rich ENK-like reactivity in the external muscle coat (Kapadia and Kapadia 1986, in foetal tissue; Lolova et al 1986;Wattchow et al 1988). ENK-reactive nerve cell bodies could be located mostly in the myenteric (Kapadia and Kapadia 1986;Dhatt and Buchan 1994;Krantis et al 1998) but also in the submucous plexuses (Crowe et al 1992).…”
Section: Introductionmentioning
confidence: 91%
“…In man, positive immunostaining for enkephalin has been predominantly found in the nerve fibers of the myenteric plexus, the circular muscle and the deep muscular Opioid receptors are present on circular muscle cells of human intestine and selectively absent from longitudinal muscle cells (82)(83)(84)(85)(86). A similar distribution of enkephalin-like immunoreactivity has also been identified in the gut of other mammalian species and was found to he intrinsic to the intestine (87-89).…”
Section: Distribution Of Opioid Peptides In Peripheral Tissuesmentioning
confidence: 99%